2020
DOI: 10.1002/aocs.12319
|View full text |Cite
|
Sign up to set email alerts
|

Production of Structured Triacylglycerol via Enzymatic Interesterification of Medium‐Chain Triacylglycerol and Soybean Oil Using a Pilot‐Scale Solvent‐Free Packed Bed Reactor

Abstract: Oils rich in medium‐ and long‐chain triacylglycerols (MLCT) serve as functional oils to help reduce body fat accumulation and weight gain. However, most of the MLCT‐rich products on the market are physical blends of medium‐ and long‐chain triacylglycerols (MCT and LCT, respectively) that are not structured triacylglycerols (TAG). In this study, an efficient pilot‐scale packed bed reactor (PBR) of immobilized lipase from Thermomyces lanuginosus (Lipozyme® TL IM, Novozymes, Bagsvaerd, Denmark) was employed for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Pilot-Scale Solvent-Free Packed Bed Reactor (PBR) was used for production of structured triacylglycerol via Enzymatic Interesterification of Medium-Chain Triacylglycerol and Soybean Oil using Lipozyme TL IM 1,3 selective enzyme [14].…”
Section: Medium -Long-chain Triglycerides (Mlcts) Structured Lipids (Sls)mentioning
confidence: 99%
See 2 more Smart Citations
“…Pilot-Scale Solvent-Free Packed Bed Reactor (PBR) was used for production of structured triacylglycerol via Enzymatic Interesterification of Medium-Chain Triacylglycerol and Soybean Oil using Lipozyme TL IM 1,3 selective enzyme [14].…”
Section: Medium -Long-chain Triglycerides (Mlcts) Structured Lipids (Sls)mentioning
confidence: 99%
“…TAG -Chromatograms diagrams are shown in Diagram 1. Structured lipids containing combinations of LCFA at sn-2 and MCFAs at the sn-1,3 position, so-called medium-long-medium (MLM) TAG, will provide lipids with high coefficient absorption [14,15]. It has been reported that MLM structured lipids have a low caloric value, and can be used to control obesity, fat malabsorption, and other metabolic disorders.…”
Section: -Tag Chromatogram Of a Blend 5%supermentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [29] produced structured low-calorie TAG by interesterification of soybean oil with TAG rich in caprylic and capric acyl groups, in solvent-free media, catalyzed by Lipozyme TL IM. This biocatalyst was used in a pilot-scale packed-bed batch reactor (to avoid particle disintegration) and reused for 25 successive batch reactions (16 min/batch).…”
Section: Batch Operational Stability Testsmentioning
confidence: 99%
“…Low-calorie SL can be produced enzymatically either (i) by acidolysis of a TAG or oil, containing long-chain fatty acids, with a medium-chain fatty acid [26], or (ii) by interesterification of a TAG or oil with methyl or ethyl esters (fatty acid methyl esters, FAME, or fatty acid ethyl esters, FAEE) of medium-chain fatty acids [27,28] or medium-chain TAG [29]. Reactions catalyzed by enzymes are carried out under mild temperatures, reducing energy consumption, leading to a decrease in the loss of temperature-sensitive molecules (substrates and/or products), and resulting in more environment-friendly and safer processes.…”
Section: Introductionmentioning
confidence: 99%